Obesity Affects the Association of Bioelectrical Impedance Phase Angle With Mortality in People Living With HIV. (January 2020) - Cogliandro, Viola; Yester, Donna; Westfall, Andrew O.; Raper, James L.; Saag, Michael S.; Henostroza, German; Overton, E. Turner; Willig, Amanda L.
Abstract: Bioelectrical impedance analysis phase angle (BIA-PA) is a valid indicator of mortality risk in people living with HIV; however, it is not known whether BIA-PA is valid for people living with HIV who are overweight or obese. We assessed whether BIA-PA differentially predicted mortality by body mass index category in participants receiving clinical care at a single site between 2000 and 2012. Change in BIA-PA from the highest versus last available phase angle was assessed using multivariate logistic regression models. Eight hundred ninety participants were included in the final analyses, with 102 deaths recorded during the study period. Decline in BIA-PA was associated with mortality in underweight and normal weight participants but not in overweight or obese participants. Additional investigation is warranted to determine the appropriate clinical BIA-PA equations and parameters to identify overweight and obese patients with increased mortality risk.